Cover Feature: Catch and Release Chemotaxis (ChemSystemsChem 2/2022). Issue 2 (30th December 2021) - Yasugahira, Yusuke; Tatsumi, Yuki; Yamanaka, Osamu; Nishimori, Hiraku; Nagayama, Masaharu; Nakata, Satoshi
Abstract : The Front Cover shows the repetition of catch and release chemotaxis, which was studied by using a self‐propelled 6‐methylcoumarin (6‐MC) disk floating on water. A tablet of Na3 PO4 placed at the bottom of the water phase acted as the chemical stimulus by inducing a variation in surface tension. The self‐propelled object, the 6‐MC disk, moves in the direction of the chemical stimulus (top left) and it is caught by the stimulus (top right), that is, by the chemical reaction between 6‐MC and OH − . When OH − is consumed, the 6‐MC disk is released from the tablet and moves towards the higher surface tension (bottom). More information can be found in the Article by Masaharu Nagayama, Satoshi Nakata and co‐workers .